2021
DOI: 10.1101/2021.04.11.439339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation of sensory hair cell specific exosomes in human perilymph

Abstract: Evaluation of hearing loss patients using clinical audiometry has been unable to give a definitive cellular or molecular diagnosis, hampering the development of treatments of sensorineural hearing loss. However, biopsy of inner ear tissue without losing residual hearing function for pathologic diagnosis is extremely challenging. In a clinical setting, perilymph can be accessed, so alternative methods for molecular characterization of the inner ear may be developed. Recent approaches to improving inner ear dia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A closely related SLC26 gene family protein, Slc26a4 -pendrin, has been shown to be present in exosomes from urine [28], indicating that structurally similar proteins can be EV-associated. Hair cells are known to produce exosomes, which encase hair cell-speci c proteins and can be detected in perilymph [29,30]. Cochlear insult, such as with noise, is known to lead to increased prestin expression in the remaining OHCs [31].…”
Section: Discussionmentioning
confidence: 99%
“…A closely related SLC26 gene family protein, Slc26a4 -pendrin, has been shown to be present in exosomes from urine [28], indicating that structurally similar proteins can be EV-associated. Hair cells are known to produce exosomes, which encase hair cell-speci c proteins and can be detected in perilymph [29,30]. Cochlear insult, such as with noise, is known to lead to increased prestin expression in the remaining OHCs [31].…”
Section: Discussionmentioning
confidence: 99%
“…The nding that the ~ 134 kDa prestin peak represents a glycosylated form of prestin is also key as glycosylated proteins are generally enriched in secreted EVs [25,26]. Hair cells are known to produce exosomes, which encase hair cell-speci c proteins and can be detected in perilymph [27,28]. Cochlear insult, such as with noise, is known to lead to increased prestin expression in the remaining OHCs [18].…”
Section: Discussionmentioning
confidence: 99%
“…The precise physiological role of exosomes is unclear, however they have been demonstrated to have pleiotropic roles in cell-cell communication, signaling, proliferation, angiogenesis, immune response and metabolism and have been shown to carry proteins, nucleic acids and metabolites (Kalluri and LeBleu, 2020;Warnecke et al, 2022). Exosomes have been recently identified, isolated and characterized from the perilymph of adult patients with various forms of SNHL or mixed hearing loss, with the study suggesting a hair cell origin of the exosomes by their expression of MYO7A (Zhuang et al, 2021). On the therapeutic side, a study from Athanasia Warnecke and colleagues demonstrated protective effects of bone marrow mesenchymal stromal cell-derived extracellular vesicles on a mouse model of NIHL, which additionally promoted neurite outgrowth in vitro (Warnecke et al, 2020).…”
Section: Emerging Interventions For Sensorineural Hearing Lossmentioning
confidence: 99%